Diabetes insipidus in pregnancy - Hague, William M (Obstet Med, 2009)
Diabetes insipidus is an uncommon condition with various aetiologies. Recent research has uncovered new mechanisms underlying the syndrome. Careful attention to management is essential in pregnant women to avoid serious complications. Diabetes insipidus in pregnancy may be due to relative reduction in secretion of AVP from the posterior pituitary (cranial DI), increase in breakdown of AVP by placental cystine aminopeptidase with vasopressinase activity, or resistance of the rental tubules to AVP (nephrogenic DI).